Coronaviral RNA-methyltransferases: function, structure and inhibition - Nencka, Radim; Silhan, Jan; Klima, Martin; Otava, Tomas; Kocek, Hugo; Krafcikova, Petra; Boura, Evzen (Nucleic acids research, 2022)
Coronaviral methyltransferases (MTases), nsp10/16 and nsp14, catalyze the last two steps of viral RNA-cap creation that takes place in cytoplasm. This cap is essential for the stability of viral RNA and, most importantly, for the evasion of innate immune system. Non-capped RNA is recognized by innate immunity which leads to its degradation and the activation of antiviral immunity. As a result, both coronaviral MTases are in the center of scientific scrutiny. Recently, X-ray and cryo-EM structures of both enzymes were solved even in complex with other parts of the viral replication complex. High-throughput screening as well as structure-guided inhibitor design have led to the discovery of their potent inhibitors. Here, we critically summarize the tremendous advancement of the coronaviral MTase field since the beginning of COVID pandemic.
Keywords: sekvence aminokyselin; Models, Molecular; objevování léků; Protein Binding; metylace; methyltransferasy; RNA, Viral; Coronavirus; Methyltransferases; Molecular Conformation; molekulární modely; vztahy mezi strukturou a aktivitou; Humans; Binding Sites; Amino Acid Sequence; molekulární konformace; vazba proteinů; molekulární struktura; Drug Discovery; aminokyseliny; Structure-Activity Relationship; Methylation; RNA virová; vazebná místa; lidé; Amino Acids; Molecular Structure